Citare i classici per non essere poeti: l’umanesimo di Francesco Berni - Chiara Cassiani (Parole Rubate, 2022)
The article examines the way in which Francesco Berni refers to the classics both in verses and in prose, aiming to identify shared motifs between his rhetorics and his poetry. The analysis shows how the spiritual tension and the opposition to classicist rules give continuity to different periods of Berni’s production, from the Roman phase in which he composed his paradoxical rhymes, to the Veronese phase in the service of Cardinal Matteo Giberti. In the crucial years of the crisis of humanism and the reform of the Church, Berni’s poetics of paradox and his references to the classics also need to be interpreted as parts of a strategy to talk about his time. Seen in this way, a number of statements in the "Dialogo contra i poeti" and in the "Comento alla Primiera" not only appear to be less contradictory, but they may also be connected to some moralizing instances and homiletic passages in the "Rifacimento of the Orlando innamorato".